2009
DOI: 10.1590/s0037-86822009000600012
|View full text |Cite
|
Sign up to set email alerts
|

Infecções humanas causadas por poxvirus relacionados ao vírus vaccinia no Brasil

Abstract: Since 1999, human infection caused by Orthopoxvirus has been observed in at least eight Brazilian states, with the presence of vesicles that evolve to pustules and crusts, especially on the hands, arms and face, after contact with cows showing comparable lesions on the udder. In addition to the skin lesions, there have been descriptions of patients with axillary ganglionic reactions that are sometimes painful, along with fever, headache, fatigue, dehydration, anorexia, sudoresis, arthralgia and muscle pain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
1
10
0
7
Order By: Relevance
“…Similar clinical symptoms were observed in humans beings in outbreaks described in other Brazilian states (Nagasse--Sugahara et al 2004, Megid et al 2008, Silva et al 2008, Schatzmayr et al 2009b). Sudoresis, anorexia, toxemia and lymph node swelling were also observed in some human cases (Silva et al 2008, Schatzmayr et al 2009a, 2009b. In comparison with other zoonotic vesicular disease, VACV infection appears to affect more severely and systematically the humans that have contact with the affected cattle (Büttner & Rziha 2002, Silva-Fernandes et al 2009).…”
Section: Discussionsupporting
confidence: 83%
“…Similar clinical symptoms were observed in humans beings in outbreaks described in other Brazilian states (Nagasse--Sugahara et al 2004, Megid et al 2008, Silva et al 2008, Schatzmayr et al 2009b). Sudoresis, anorexia, toxemia and lymph node swelling were also observed in some human cases (Silva et al 2008, Schatzmayr et al 2009a, 2009b. In comparison with other zoonotic vesicular disease, VACV infection appears to affect more severely and systematically the humans that have contact with the affected cattle (Büttner & Rziha 2002, Silva-Fernandes et al 2009).…”
Section: Discussionsupporting
confidence: 83%
“…No período de estação seca há possibilidade de maior ocorrência de traumatismos nas tetas, pois a pele pode apresentar-se ressecada, aumentando o número das soluções de continuidade e abrindo caminho para infecção viral (DAMASO et al, 2000;SCHATZMAYR et al, 2000;TRINDADE et al, 2003).…”
Section: Resultsunclassified
“…O uso de luvas de borracha deve ser incentivado. A introdução de animais no rebanho deve ser acompanhada por uma rigorosa inspeção nas tetas dos animais, buscando lesões compatíveis com doença (DAMASO et al, 2000;SCHATZMAYR et al, 2000;TRINDADE et al, 2003;FERREIRA et al, 2008) De acordo com os autores uma ferramenta muito importante no controle desta doença é o nível de informação do médico veterinário e dos proprietários das fazendas e/ou propriedades agrícolas, ou seja, o conhecimento da possibilidade de ocorrência desta doença e suas características, facilitando assim o diagnóstico precoce dentro de uma propriedade ou área geográfica e possibilitando a aplicação de medidas de prevenção.…”
Section: Resultsunclassified
“…It is likely that the vaccine strains have been introduced into nature more than once. Over the years, several authors have confirmed the presence of infections in animals and humans by poxvirus, particularly in the Brazilian southeast (Mello et al 1960, Schatzmayr et al 2009a, 2009b, 2011Silva & Moraes 1962, Trindade et al 2003, Donatele et al 2007). It must be remembered that the smallpox vaccination campaign was discontinued in the country in the 1970s, which confirms that the vaccinialike virus is circulating in the country, a fact accepted in the international literature (Regnery 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Damaso et al (2000) have shown that the virus, called Cantagalo (CTGV), isolated in municipalities with animals exhibiting vesicular/pustular disease is an Orthopoxvirus and that at the molecular level, this virus is very close to the sample vaccinia virus used in the past to prepare vaccines at the Instituto Oswaldo Cruz. Later, other authors confi rmed the circulation of similar viruses as a cause of infection in animals and humans, especially in the state of Rio de Janeiro and throughout southeastern Brazil (Costa et al 2007, Donatele et al 2007, Leite et al 2005, Nagasse-Sugahara et al 2004, Schatzmayr et al 2009a, Schatzmayr et al 2009b, Schatzmayr et al 2011, Trindade et al 2003, Trindade et al 2006, Trindade et al 2007. Th e movement of vaccinia virus has been confi rmed in the Brazilian territory and by reports in the international literature (Regnery 2007).…”
Section: Introductionmentioning
confidence: 97%